IMPLIKASI CAFTA TERHADAP PRODUK JADI INDONESIA DI TIKTOK SHOP: TINJAUAN LITERATUR - Kamila, Noni; Muhammad Muchlis, Madian (Berajah Journal, 2024)
The implications of the China-ASEAN Free Trade Area Agreement no longer only impact conventional economic transactions, but have also impacted digital economic transactions in Indonesia. The emergence of social e-commerce is an application with dual functions: as a social media application as well as an online shopping application which in this case is TikTok with its TikTok Shop feature is very troubling for micro, small and medium enterprises in Indonesia. Therefore, this research will examine the impact of the China-ASEAN Free Trade Area agreement on online buying and selling transactions via TikTok Shop. The data collection method used is the literature review method (library research). This type of research is descriptive research through a qualitative approach. The impact of the Free Trade Area coupled with the penetration of imported goods directly (cross border) from China has resulted in the proliferation of finished products offered at prices that are much cheaper to below the cost of production of local finished products for similar products. This affects the competitiveness of micro, small and medium enterprises.